Examining and Solving Health Disparities in the United States: Emerging Research and Opportunities - Green, Cheryl (Medical Information Science Reference, 2021)
"This book provides awareness and discussion on the topic of inequities in healthcare that impact health disparities"--
Keywords: Health status indicators; United States; Health Status Disparities; Healthcare Disparities; United States; Health services accessibility; dept.nur; economics; Health Services Accessibility; economics; Socioeconomic Factors; Minority Health; United States; faculty_collection